Algorithm Governance Framework for Media Regulation in Nigerian Media System - Bashir, Abdullahi Saleh (The Journal of Society and Media, 2020)
The world of media and information, from the time internet became popular, has been in constant rapid changes to such an extent that older models of conventional media system are being challenged if not replaced. One of the changes being experienced in the contemporary media environment is the use of computer codes or algorithms to perform gatekeeping functions that used to be done solely by human agents. This paper reviews the state and challenges of media regulations and the use of algorithms in Nigerian media system. The review showed a gap in media regulation in Nigeria where journalism is compartmentalised in contrast to media convergence and that algorithmic-based journalism may not be effectively regulated. To close this gap, the study used risk-based analysis as a theoretical framework and library research as method to design a framework for algorithmic media governance in the country. The result is the Converged Media Governance Framework for Algorithmic and Mixed Journalism. The framework reconceptualizes the way and manner media regulation is framed and organised as involving only human agents and alsothat journalism in the country should not be compartmentalised in the light of media convergence. The paper recommended the adoption of the framework by stakeholders in the Nigerian media system.